2021
DOI: 10.3390/agronomy11020393
|View full text |Cite
|
Sign up to set email alerts
|

Can Hydromulch Reduce the Emergence of Perennial Weeds?

Abstract: Herbicide weed control is difficult in the first years of perennial crop establishment or in minor crops, and plastic sheet mulches can leave persistent residues. Liquid spray-on mulch (hydromulch) might be a solution in these cases. To test three hydromulch formulations on perennial weed emergence, greenhouse assays were conducted for two years in two localities to evaluate their rhizome sprouting and shoot emergence. Data, obtained from a completely randomized block design, were analyzed by means of generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Additionally, the hydromulch treatment (12 weeks after planting) maintained the lowest weed cover (22%) compared to no mulch (36%), gin trash (52%), and wheat straw (72%) treatments (Henry and Hoyle, 2021). The results from the present study were also consistent with Mas et al (2021), where hydromulch treatments (rice husk and used mushroom substrate) suppressed weed rhizome sprouting (55% and 56%, respectively) compared to a non-mulch treatment (72% sprouting rate of weed rhizomes).…”
Section: Weed Suppression Efficacysupporting
confidence: 87%
“…Additionally, the hydromulch treatment (12 weeks after planting) maintained the lowest weed cover (22%) compared to no mulch (36%), gin trash (52%), and wheat straw (72%) treatments (Henry and Hoyle, 2021). The results from the present study were also consistent with Mas et al (2021), where hydromulch treatments (rice husk and used mushroom substrate) suppressed weed rhizome sprouting (55% and 56%, respectively) compared to a non-mulch treatment (72% sprouting rate of weed rhizomes).…”
Section: Weed Suppression Efficacysupporting
confidence: 87%
“…The doses of the different components for the mixtures can be found in a previous paper [3], with the exception of the pistachio and the vineyard pruning wood chips, which were 1060 g m −2 in both cases.…”
Section: Trial Descriptionmentioning
confidence: 86%
“…In the same crop, it was also found that hydromulch composed of mushroom by-products combined with the inoculation of a type of mycorrhizae improved the growth of escarole [10]. Using the same mixtures to test perennial weed emergence, it was observed that these materials reduced the appearance of certain weed species, confirming their potential to be used as a non-chemical weed control method [3]. From an economic point of view, it was concluded that the use of hydromulches in artichoke crop cultivation is more sustainable and profitable, as well as environmentally friendly, than traditional polyethylene mulching, although the availability of plant waste in the area where hydromulching is used is important for its economic viability [11].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hydromulching can be useful for the suppression of weed growth, where mechanical and chemical weeding are very difficult [31,32]. Hydromulches can persist for a long time on the ground, although this depends on environmental factors (temperature and moisture) [33].…”
Section: Introductionmentioning
confidence: 99%